Cognitive and motivational bias in Budgetary Decision Making: Experimental Evidence in the Public Sector - BORGES DE ARAUJO, FERNANDA; dos Anjos, Luiz Carlos Marques (Advances in Scientific and Applied Accounting, 2025)
Objective: To investigate how various cognitive and motivational biases affect decisions regarding budget expenditure and public administration. The nature of the experimental task consisted of manipulating hypothetical decision-making situations, in a realistic scenario, with the aim of verifying whether the biases: anchoring, status quo, framing and overconfidence were manifested in the managers’ responses. Method: A within-participants experiment was carried out, with data collected through a survey applied to members of the college of directors - managers, with more than five years in the role. The independent variable “knowledge” was manipulated, and “experience” measured, using concrete situations. Results: It was found that managers’ decision-making and their judgments about the execution of public expenditure were influenced by cognitive and motivational biases; certifying that managers were overconfident, even when making wrong decisions. Contributions: For behavioral public administration, progress in management policies and organizations implies advances in managerial decision-making. The expansion of the scope, so that the manipulations carried out reflect real decision-making situations, allows us to understand how those responsible for the execution of expenses in the managed units actually decide on the allocation of resources.